2018
DOI: 10.1186/s12882-018-1029-8
|View full text |Cite
|
Sign up to set email alerts
|

The two isoforms of matrix metalloproteinase- 2 have distinct renal spatial and temporal distributions in murine models of types 1 and 2 diabetes mellitus

Abstract: BackgroundWe recently reported on the enhanced tubular expression of two discrete isoforms of the MMP-2 (full length and N-terminal truncated, FL-MMP-2, NTT-MMP-2) in a murine model and human diabetic kidneys. In the present study, we examined in more detail the temporal and spatial distributions of MMP-2 isoform expression in murine models of Type 1 and Type 2 diabetes mellitus.MethodsDiabetic models were streptozotocin (STZ)-induced diabetes (Type 1 diabetes mellitus) and db/db mice (Type 2 diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…qPCR. qPCR was performed as described previously (Kim et al 2018;Rahman et al 2018). In brief, total RNA was extracted from the frozen tissue of A21a using the RNAprep Pure Tissue Kit (Tiangen Biotech, Beijing, China) and reverse transcription was performed on 2 μL of total RNA using the FastQuant RT Kit (with gDNase) (Tiangen Biotech) in accordance with the manufacturer's instructions.…”
Section: Measurement Of the Expression Of Gaba-and Glu-synthesizing Ementioning
confidence: 99%
See 2 more Smart Citations
“…qPCR. qPCR was performed as described previously (Kim et al 2018;Rahman et al 2018). In brief, total RNA was extracted from the frozen tissue of A21a using the RNAprep Pure Tissue Kit (Tiangen Biotech, Beijing, China) and reverse transcription was performed on 2 μL of total RNA using the FastQuant RT Kit (with gDNase) (Tiangen Biotech) in accordance with the manufacturer's instructions.…”
Section: Measurement Of the Expression Of Gaba-and Glu-synthesizing Ementioning
confidence: 99%
“…The sequences of the primers used in the RT-PCR are listed in Table 1. The relative mRNA concentration of the target genes was calculated vs. the corresponding GAPDH Ct value and expressed in a 2 − Ct method (Kim et al 2018;Rahman et al 2018).…”
Section: Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were attenuated by renin-angiotensin system (RAS) inhibition [58]. Recently, two different isoforms of MMP-2 were identified in diabetic models showing differentially distribution in renal tissue [59]. An interesting finding on genetic susceptibility to DKD was described by Fornoni et al, who analysed mesangial cells from murine strains resistant (B6) and susceptible (ROP) to sclerosis, mimicking patients who develop DKD despite an adequate glycaemic control.…”
Section: Mmps In Experimental Diabetic Nephropathymentioning
confidence: 99%
“…Also, different conditions and time of evolution of disease [57] are presented according to in vitro or in vivo models. Moreover, it has been reported that murine strains may also show certain discrepancies in MMPs outcomes according to the genetic background [59].…”
Section: IIImentioning
confidence: 99%